1999
DOI: 10.1074/jbc.274.34.23883
|View full text |Cite
|
Sign up to set email alerts
|

The L1Tc, Long Interspersed Nucleotide Element from Trypanosoma cruzi, Encodes a Protein with 3′-Phosphatase and 3′-Phosphodiesterase Enzymatic Activities

Abstract: The presence of a long interspersed nucleotide element, named L1Tc, which is actively transcribed in the parasite Trypanosoma cruzi, has been recently described. The open reading frame 1 of this element encodes the NL1Tc protein, which has apurinic/apyrimidinic endonuclease activity and is probably implicated in the first stage of the transposition of the element. In the present paper we show that NL1Tc effectively removes 3 -blocking groups (3 -phosphate and 3 -phosphoglycolate) from damaged DNA substrates. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…C2-L1Tc may neutralize the negative charge of the DNA phosphodiester backbone, facilitating association of DNA strands, stabilizing the formed duplex by charge shielding, and increasing the melting temperature of perfect duplex when complementary primers are used. Moreover, C2-L1Tc allows the formation of the most stable duplex, promoting the exchange of strands when both 32 P29-25c and 29-32 Pmm29 preformed duplex and an excess of single-stranded complementary 29c are used, even though it has no effect on the melting temperature of [29][30][31][32] Pmm29 mismatched duplexes in melting assays. This result suggests that C2-L1Tc produces the strand exchange by means of specific interactions with nucleic acids and by a transient base-pair destabilization, thereby allowing a subsequent partial base pairing and displacement of the less homologous primer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C2-L1Tc may neutralize the negative charge of the DNA phosphodiester backbone, facilitating association of DNA strands, stabilizing the formed duplex by charge shielding, and increasing the melting temperature of perfect duplex when complementary primers are used. Moreover, C2-L1Tc allows the formation of the most stable duplex, promoting the exchange of strands when both 32 P29-25c and 29-32 Pmm29 preformed duplex and an excess of single-stranded complementary 29c are used, even though it has no effect on the melting temperature of [29][30][31][32] Pmm29 mismatched duplexes in melting assays. This result suggests that C2-L1Tc produces the strand exchange by means of specific interactions with nucleic acids and by a transient base-pair destabilization, thereby allowing a subsequent partial base pairing and displacement of the less homologous primer.…”
Section: Discussionmentioning
confidence: 99%
“…L1Tc is actively transcribed in the three stages of the parasite life cycle (21) and codes for the enzymatic machinery involved in its retrotransposition including AP endonuclease, 3Ј phosphatase, 3Ј phosphodiesterase (28,31), reverse transcriptase (RT) (13), and RNase H (29) activities. The C-terminal domain of the L1Tc element contains two cysteine motifs of the C 2 H 2 type, which are structurally homologous to the zinc fingers of transcription factors of multicellular organisms (21).…”
mentioning
confidence: 99%
“…Furthermore, it has been shown that L1Tc also carries 3)-phosphodiesterase and 3)-phosphatase activities, which remove 3)-blocking groups (3)-phosphate and 3)-phosphoglycolate) from the 3) ends of damaged DNA substrates, theoretically allowing them to function as target sites for the insertion of L1Tc elements (Olivares et al, 1999). It was postulated that the presence of the 3) repair activities associated with L1Tc endonuclease protein could be indicative of a possible role of the L1Tc element in DNA repair (Olivares et al, 1999).…”
Section: L1tc Endonuclease From T Cruzimentioning
confidence: 99%
“…L1Tc from Trypanosoma cruzi encodes a domain that has a true AP endonuclease activity; it has been shown to cleave apurinic/apyrimidinic (AP) sites, indicating a possible role of L1Tc in DNA repair (88). However, other APE-encoding non-LTR elements appear to have lost this intrinsic enzymatic activity.…”
Section: Molecular Mechanism Of Sequence-specific Retrotransposition mentioning
confidence: 99%